Disentangling Bulk and Interface Phenomena in a Molecularly Doped Polymer Semiconductor. Issue 14 (2nd February 2021) - Lungwitz, Dominique; Schultz, Thorsten; Tait, Claudia E.; Behrends, Jan; Mohapatra, Swagat K.; Barlow, Stephen; Marder, Seth R.; Opitz, Andreas; Koch, Norbert
Abstract: Doping the electron‐transport polymer poly{[ N, N ′‐bis(2‐octyldodecyl)naphthalene‐1, 4, 5, 8‐bis(dicarboximide)‐2, 6‐diyl]‐alt‐5, 5′‐(2, 2′‐bithiophene)} [P(NDI2OD‐T2 )] with the bulky, strongly reducing metallocene 1, 2, 3, 4, 1′, 2′, 3′, 4′‐octaphenylrhodocene (OPR) leads to an increased bulk conductivity and a decreased contact resistance. While the former arises from low‐level n‐doping of the intrinsic polymer and increased carrier mobility due to trap‐filling, the latter arises from a pronounced accumulation of dopant molecules at an indium tin oxide (ITO) substrate. Electron transfer from OPR to ITO leads to a work function reduction, which pins the Fermi level at the P(NDI2OD‐T2 ) conduction band and thus minimizes the electron injection barrier and the contact resistance. The results demonstrate that disentangling the effects of electrode modification by the dopant and bulk doping is essential to comprehensively understand doped organic semiconductors. Abstract : When spin‐coated from mixed solution, the bulky octaphenylrhodocene (OPR) metallocene is a weak n‐type dopant for the conjugated polymer poly{[ N, N ′‐bis(2‐octyldodecyl)naphthalene‐1, 4, 5, 8‐bis(dicarboximide)‐2, 6‐diyl]‐alt‐5, 5′‐(2, 2′‐bithiophene)} [P(NDI2OD‐T2 )], and simultaneously reduces the work function of indium‐tin‐oxide (ITO) to 3.9 eV for enhanced electron injection.